International Education and the Global Pandemic in the Community College: Reflections and Best Practices (Comparative & International Education Series, 2021)
Chapter 12|16 pages International Education and the Global Pandemic in the Community College: Reflections and Best PracticesBy Marc ThomasThis chapter presents an overview of how American community colleges responded to the COVID-19 pandemic in early 2020, while focusing on the effect the pandemic had on international students in the United States. This chapter also offers examples of best practices reported by international education practitioners and reviews research-based evidence that has guided higher education international study during the 21st century.